CCUS evaluation and simulation in a Chinese oil field. (2018) - Lu, Shijian; Zhao, Dongya; Cui, Wenhao; Li, Zhaomin; Zhu, Quanmin
This paper studies the evaluation issue of a preparatory CCUS in China. Economic and environmental evaluation are presented with the delicate simulations. The analysis of the evaluation results show that the CCUS project will be feasible if the oil price is high enough or the storage allowance can be given. The results will be useful for the future CCUS projects and will be useful for the government decisions on CCUS.